Quercetin: a natural remedy against high-fat diet-induced liver steatosis in Oncorhynchus mykiss - Özay Köse (Frontiers in Marine Science)
IntroductionThis study investigated the effects of a high-fat diet (HFD) on hepatic steatosis and the protective role of quercetin (3,3′,4′,5,7-pentahydroxyflavon) in juvenile female rainbow trout (Oncorhynchus mykiss).MethodsA total of 270 fish were randomly divided into three dietary groups and fed for 8 weeks: low-fat diet (LFD; 11.38% crude fat, 0 g/kg quercetin), high-fat diet (HFD; 22.53% crude fat, 0 g/kg quercetin), and high-fat diet supplemented with quercetin (HFD+Q; 22.33% crude fat, 0.20 g/kg quercetin). Growth performance, serum biochemical parameters, hepatic histomorphology, antioxidant enzyme gene expressions, and lipid metabolism-related gene expressions were evaluated.ResultsHFD and HFD+Q diets positively supported fish growth with a protein-sparing effect. However, it increased organosomatic indices, but this increase was limited to HFD+Q supplemented with quercetin. In this study, a high-fat diet (HFD) induced hepatic steatosis characterized by significant lipid accumulation, elevated non-esterified free fatty acid (NEFA) levels in liver tissue (p<0.05), increased serum levels of low-density lipoprotein (LDL), cholesterol, and triglycerides (TG), structural alterations in liver histomorphology such as hepatocyte vacuolization, nuclear degeneration, and sinusoidal dilation, enhanced activities of hepatic enzymes including alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), and lactate dehydrogenase (LDH), as well as upregulation of cysteine-aspartate-specific protease-3 (caspase-3) mRNA expression (p<0.05). Quercetin prevented and alleviated the main metabolic and pathological changes induced by the HFD. Quercetin supplementation significantly reduced serum lipid profiles, hepatic lipid accumulation, NEFA levels, ALT, AST, ALP, and LDH enzyme activities, and downregulated caspase-3 gene expression compared to the HFD group (p<0.05). Gene expression analysis revealed that quercetin upregulated lipolysis and β-oxidation-related genes including peroxisome proliferator-activated receptor alpha (ppar-α), carnitine palmitoyltransferase-1a (cpt-1a), and hormone-sensitive lipase (hsl), while downregulating lipogenesis-associated genes fatty acid synthase (fas) and lipoprotein lipase (lpl) (p<0.05). Regarding antioxidant defense, quercetin supplementation decreased superoxide dismutase (sod) and glutathione S-transferase (gst) mRNA levels, increased catalase (cat) expression, but the suppression of glutathione peroxidase (gpx) expression persisted (p<0.05).DiscussionThese findings suggest that the HFD diet disrupts oxidative balance by increasing oxidative stress and impairing antioxidant systems, while quercetin ameliorates oxidative imbalance and mitigates hepatic damage. In conclusion, quercetin exerts hepatoprotective effects against HFD-induced hepatic steatosis by targeting lipid accumulation, oxidative stress, and apoptosis pathways, supporting its potential as a dietary supplement to prevent hepatic steatosis in aquaculture.